Pembelajaran dalam Jaringan (DARING) Berbasis WhatsApp di SD Yapita - Arindra Evandian Bhagaskara; Eka Nur Afifah; Enggar Maulana Putra (ZAHRA: Research and Tought Elementary School of Islam Journal, 2021)
The learning process at the time COVID-19 must be implemented online. The use of media in learning is very important. The whatsapp application was chosen to be used in this online learning. This study aims to obtain information about the application of the WhatsApp application in online learning and to find out what are the advantages and disadvantages of using the WhatsApp application in online learning. The research subjects here are the teachers and students of SD Yapita Surabaya and the object under study is the use of the WhatsApp application in online learning. This study used a qualitative research design. The instruments used in this study were observation, surveys and interviews. The results obtained are that the application WhatsApp can be applied in the learning process online and there are also deficiencies in its application, namely the existence of obstacles regarding face-to-face implementation through the existing features of the WhatsApp application and the absence of features to limit student work time and for the advantages the WhatsApp application is able to accommodate the implementation of the learning process well.